Self-management in patients with diabetes mellitus - Mikšová, Zdeňka; Reiterová, Eva; Buchtíková, Jana; Konečná, Jana; Školoudík, David (Profese Online, 2018)
Background: In the Czech Republic, the incidence of new cases of diabetes mellitus is rising. It is desirable for patients to manage the control and management of their illnesses. Thus, education in the area of self-management is important, which requires appropriate support from health professionals, especially nurses. The Partners in Health Scale (PIH, Health Partner Scale) can be used to evaluate self-management. The scale identifies areas of self-care reserves and patient self-regulation. Objective: The objective is to verify the reliability and internal consistency of the PIH scale in the socio - cultural conditions of the Czech Republic and to describe the level of self - management in patients with type 2 diabetes mellitus. Methods: A structured questionnaire containing the Czech version of Partners in Health Scale was used as part of a quantitative cross-sectional prospective study. Results: The survey was attended by 58 respondents who met the inclusion and exclusion criteria of the study. The high reliability and internal consistency of the Czech version of PIH has been demonstrated. The best results were the proband in the field of monitoring the course of the disease and respecting the treatment regimen. The link between education and the financial situation and the level of self-determination has been demonstrated. There was no difference between men and women and the overall level of self-management. Conclusion: The PIH scale is a suitable tool for determining the level of self-management in patients with type 2 diabetes mellitus in the socio-cultural conditions of the Czech Republic.
Keywords: Self-management; diabetes mellitus; PIH scale; self-care; self-regulation